Public commissions on cultural and religious diversity National narratives, multiple identities and minorities - Alidadi, Katayoun; Foblets, Marie-Claire (Routledge, 2018)
Building on its companion volume (Public Commissions on Cultural and Religious Diversity: Analysis, Reception and Challenges), this book engages with core concepts of identity, nationality, citizenship, freedom, equality and accommodation. It will appeal to researchers and students of public policy, sociology, anthropology, law, religion, politics, history and migration studies, as well as policymakers and anyone with a general interest in current debates on ethnic, cultural and religious diversity.